2016
DOI: 10.1002/adsc.201600039
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed [2+2+2] Cycloadditions of Diynes with Morita–Baylis–Hillman Adducts: A Stereoselective Entry to Densely Functionalized Cyclohexadiene Scaffolds

Abstract: A rhodium-catalyzed asymmetric synthesis of 5,5-disubstituted cyclohexa-1,3-dienes has been achieved by [2+2+2] cycloaddition reactions between diynes and Morita-Baylis-Hillman (M-B-H) adducts as unsaturated substrates. Products containing two adjacent chiral centres (quaternary and tertiary, respectively) were obtained with complete diastereoselectivity and high enantioselectivity (84-97%) through a kinetic resolution of the M-B-H adduct. Furthermore, these highly substituted cyclohexadienes reacted with dien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In 2016, Roglans and Pla‐Quintana reported that racemic secondary allylic alcohols react with 1,6‐diynes through the kinetic resolution in the presence of a cationic rhodium(I)/binap complex to give bicyclic cyclohexadienes (Scheme b) . This reaction can construct contiguous two stereogenic centers as a single diastereomer with high ee values, while the substrate scope was somewhat limited (methoxycarbonyl‐ and aryl‐substituted allylic alcohols, and sulfonamide‐linked and dimethyl‐substituted 1,6‐diynes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Roglans and Pla‐Quintana reported that racemic secondary allylic alcohols react with 1,6‐diynes through the kinetic resolution in the presence of a cationic rhodium(I)/binap complex to give bicyclic cyclohexadienes (Scheme b) . This reaction can construct contiguous two stereogenic centers as a single diastereomer with high ee values, while the substrate scope was somewhat limited (methoxycarbonyl‐ and aryl‐substituted allylic alcohols, and sulfonamide‐linked and dimethyl‐substituted 1,6‐diynes).…”
Section: Methodsmentioning
confidence: 99%
“…[6, 7a, 9] In 2016, Roglans andP la-Quintana reported that racemic secondary allylic alcohols [10] react with 1,6-diynes through the kinetic resolution [11] in the presenceo facationic rhodium(I)/ binap complex to give bicyclic cyclohexadienes (Scheme 1b). [12] This reactionc an construct contiguous two stereogenic centers as as ingled iastereomer with high ee values, whilet he substrate scope was somewhat limited( methoxycarbonyl-and aryl-substituted allylic alcohols, ands ulfonamide-linked and dimethyl-substituted 1,6-diynes).Inthis Communication, we have established that ac ationic rhodium(I)/Pphos complex is capableo fc atalyzing the regio-,d iastereo-, and enantioselective [2+ +2+ +2] cycloaddition of 1,6-enynes with racemic secondary allylic alcohols through the kineticr esolution at room temperature giving chiralb icyclic cyclohexenes, possessing three stereogenic centers (Scheme 1c). This newly developed asymmetric catalysis shows ab road substrate scope concerning both 1,6-enyes and allylic alcohols.…”
mentioning
confidence: 99%
“…), with an excellent yield of 95% of 7. Considering the potential of alkenes as unsaturations in these processes, one of our contributions in this field, again in collaboration with the Muzart's group in Reims, has been the use of Morita-Baylis-Hillman (MBH) adducts 64 as alkenes (Scheme 14) [40]. These derivatives are densely functionalized molecules, containing at least three functional groups in proximity.…”
Section: Combinations Of Rh Complexes With Phosphinesmentioning
confidence: 99%
“…They are usually generated in situ in a nonpolar solvent, either DCM or dichloroethane, by hydrogenation of a cationic bis-diolefin rhodium complex, for example, [Rh(COD) 2 ]OTf, in the presence of a diphosphine like BINAP. ([2+2+2]cycloadditions: [176][177][178][179][180][181][182][183][184], hydrogen-mediated reductive C-C coupling: [185][186][187], enantioselective reductive cyclization: [188,189], intermolecular cyclotrimerization: [190][191][192][193]) It should be noted that the formation of these species and their role in catalysis is often overlooked.…”
Section: +mentioning
confidence: 99%